The Talisman - Scott, Walter; Alexander, J. H.; Ellis, J. B.; Hewitt, David (Edinburgh : Edinburgh University Press, 2022)
I found revisiting The Talisman, set in the Third Crusade before the siege of Acre, an exciting and enthralling experience, the suspense building from the novel's remarkable opening to the revelations as it nears its conclusion. The depictions of Sir Kenneth/Prince David, Richard Coeur de Lion, Saladin, and the Templar are admirably wrought and the central paradox at the heart of the novel is a striking one; in Judith Wilt's words "the Christian chivalric ideal embodies itself, arrow within secret desert leaves, in the Arab Saladin, and its enemy is the atheist warrior priest, the Templar"." - European Romantic ReviewThe second volume in the Tales of the Crusaders, The Talisman is set in Palestine during the Third Crusade (1189-92). Scott constructs a story of chivalric action, apparently adopting a medieval romance view of the similarities in the values of both sides. But disguise is the leading theme of the tale: it is not just that characters frequently wear clothing that conceals their identity, but that professions and cultures hide their true nature. In this novel the Christian leaders are divided by a factious criminality, and are contrasted to the magnanimity and decisiveness of Saladin, the leader of the Moslem armies. In a period when the west was fascinated with the exotic east, Scott represents the Moslem other as more humane than the Christian west.The Talisman is one of Scott's great novels. It is a superb tale. It is also a bold departure as, for the first time, Scott explores not cultural conflict within a country or society but in the opposition of two world religions.Find Out What Scott Really WroteGoing back to the original manuscripts, a team of scholars has uncovered what Scott originally wrote and intended his public to read before errors, misreadings and expurgations crept in during production:A clean, corrected textTextual historiesExplanatory notesVerbal changes from the first-edition textFull glossaries"
Frontmatter -- FOREWORD -- CONTENTS -- ACKNOWLEDGEMENTS -- General Introduction -- Volume I -- Volume II -- Essay on the Text -- Emendation List -- End-of-line Hyphens -- Historical Note -- Explanatory Notes -- Glossary
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Mai 2022).
eBooks on EBSCOhost
Keywords: Crusades -- Third, 1189-1192 -- Fiction; Scottish fiction -- 19th century; Literary Studies; Croisades -- 3e croisade, 1189-1192 -- Romans, nouvelles, etc; Roman écossais -- 19e siècle.; LITERARY CRITICISM / General